Datos primarios de: Four highland species of Galianthe (Rubiaceae: Spermacoceae) with restricted distribution in South America: conservation assessment and complete descriptions - Florentín, Javier Elias (2023)
Datos primarios del artículo: Four highland species of Galianthe (Rubiaceae: Spermacoceae) with restricted distribution in South America: conservation assessment and complete descriptions. Fotos (lupa, microscopio electrónico de barrido MEB, distribuciones geográficas, etc.